Population distribution of lifetime risk of ovarian cancer in the United States - Pearce, Celeste Leigh; Stram, Daniel O.; Ness, Roberta B.; Stram, Douglas A.; Roman, Lynda D.; Templeman, Claire; Lee, Alice W.; Menon, Usha; Fasching, Peter; Mcalpine, Jessica N.; Doherty, Jennifer A.; Modugno, Francesmary; et al. (Cancer Epidemiology Biomarkers & Prevention, 2015)
In U.S. women, lifetime risk of ovarian cancer is 1.37%, but some women are at a substantially lower or higher risk than this average.We have characterized the distribution of lifetime risk in the general population. Published data on the relative risks and their variances for five well-accepted risk and protective factors for ovarian cancer, oral contraceptive use, parity, tubal ligation, endometriosis, and first-degree family history of ovarian cancer in conjunction with a genetic risk score using genome-wide significant common, low penetrance variants were used. The joint distribution of these factors (i.e., risk/protective factor profiles) was derived using control data from four U.S. population-based studies, providing a broad representation of women in the United States.A total of 214 combinations of risk/protective factors were observed, and the lifetime risk estimates ranged from 0.35% [95% confidence interval (CI), 0.29-0.42] to 8.78% (95% CI, 7.10-10.9). Among women with lifetime risk ranging from 4% to 9%, 73% had no family history of ovarian cancer; most of these women had a self-reported history of endometriosis.Profiles including the known modifiable protective factors of oral contraceptive use and tubal ligation were associated with a lower lifetime risk of ovarian cancer. Oral contraceptive use and tubal ligation were essentially absent among the women at 4% to 9% lifetime risk.This work demonstrates that there are women in the general population who have a much higher than average lifetime risk of ovarian cancer. Preventive strategies are available. Should effective screening become available, higher than average risk women can be identified.
EVALuna2:17564